The Attenuation of Traumatic Brain Injury via Inhibition of Oxidative Stress and Apoptosis by Tanshinone IIA. (4th May 2020) - Huang, Yongpan; Long, Xian; Tang, Jiayu; Li, Xinliang; Zhang, Xiang; Luo, Chunyan; Zhou, Yan; Zhang, Pan
Abstract : Traumatic brain injury (TBI) is a major source of mortality and long-term disability worldwide. The mechanisms associated with TBI development are poorly understood, and little progress has been made in the treatment of TBI. Tanshinone IIA is an effective agent to treat a variety of disorders; however, the mechanisms of Tanshinone IIA on TBI remain unclear. The aim of the present study was to investigate the therapeutic potential of Tanshinone IIA on TBI and its underlying molecular mechanisms. Changes in microvascular permeability were examined to determine the extent of TBI with Evans blue dye. Brain edema was assessed by measuring the wet weight to dry weight ratio. The expression levels of CD11, interleukin- (IL-) 1 β, and tumor necrosis factor- (TNF-) α mRNA were determined by reverse transcription-quantitative PCR. Aquaporin-4 (AQP4), glial fibrillary acidic protein (GFAP), and p47phox protein expression levels were detected by western blotting. Superoxide dismutase (SOD), catalase and glutathione peroxidase (GSH-PX) activities, and malondialdehyde (MDA) content were determined using commercial kits. Cell apoptosis was detected by western blotting and TUNEL staining. Tanshinone IIA (10 mg/kg/day, intraperitoneal administration) significantly reduced brain water content and vascular permeability at 12, 24, 48, and 72 h after TBI. Tanshinone IIA downregulated the mRNA expression levels of various factors induced by TBI, including CD11, IL-1 β, and TNF- α . Notably, CD11 mRNA downregulation suggested that Tanshinone IIA inhibited microglia activation. Further results showed that Tanshinone IIA treatment significantly downregulated AQP4 and GFAP expression. TBI-induced oxidative stress and apoptosis were markedly reversed by Tanshinone IIA, with an increase in SOD and GSH-PX activities and a decrease in the MDA content. Moreover, Tanshinone IIA decreased TBI-induced NADPH oxidase activation via the inhibition of p47phox. Tanshinone IIA attenuated TBI, and its mechanism of action may involve the inhibition of oxidative stress and apoptosis.